Effects of the extreme environment of volcanic origin in organisms : using earthworms as biological models - Cunha, Luis Filipe das Neves (2017)
Tese de Doutoramento, Biologia (Biologia Celular e Molecular), 18 de Maio de 2012, Universidade dos Açores.